Soft Switching Boost Converter Solution for Increase the Efficiency of Solar Energy Systems - Alireza Kaviani-Arani; Alireza Gheiratmand (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
Nowadays, renewable energies are considered as an important source of non-polluting and free energy. Solar energy in the form of photovoltaic systems is one of the most prominent of them. Using this type of energy can be an affordable and suitable solution to supply electricity to the consumers who do not have access to the distribution network due to geographical conditions. Regarding to low efficiency and high cost of installing solar panels, receiving the maximum power of them is taken into consideration. DC-DC converters are one of the key components of solar energy systems. These converters have the switching losses and their efficiency is not so high. This paper explores the switching losses in hard switching boost converter and by providing a soft switching boost converter, reduces switching losses and increases the efficiency of solar energy systems. The performance of the converter has been studied and simulations indicate its performance. DOI: http://dx.doi.org/10.11591/telkomnika.v13i3.7127